Aerodynamics of a new volleyball - Asai, T.; Ito, S.; Seo, K.; Hitotsubashi, A. (Procedia Engineering, 2010)
The purpose of this study is to analyze the basic aerodynamic characteristics of conventional balls and new balls, using a wind tunnel for the experiments. We found that the critical Reynolds number for conventional balls was approximately 270,000, and that for new balls was approximately 220,000. The drag coefficient of new balls at supercritical regime was about 0.17, showing a slightly higher value than for conventional balls. Comparing the deviation of coordinate values at the landing point of the ball in flight near the critical Reynolds regime, the new balls tended to have a smaller deviation than conventional balls.